Mathematics education in the digital age: How to foster higher-order thinking skills? - Wanda Nugroho Yanuarto; Eka Setyaningsih; Akhmad Jazuli; Elfis Suanto (International Journal of Evaluation and Research in Education (IJERE), 2023)
How technology and industrial change affect how well students do in school for the 4.0 level to be met, students must be able to use higher-order thinking and technological pedagogical content knowledge (TPACK). Students have difficulty using advanced technological tools when they need to think critically and artistically. So, students will only be able to learn higher-order thinking skills if they have TPACK. It is a common reason why people need to learn mathematics better in the current world. The purpose of this research was to help complete a structural model of TPACK and higher-order thinking skills for distance math learners. In a cross-sectional quantitative study, the data were looked at with structural equation modelling (SEM). For this study, 279 people from Universitas Muhammadiyah Purwokerto and Universitas Riau were chosen to participate. The study’s structure model shows a powerful link between higher-order thinking skills and TPACK. As a result, secondary school mathematics educators can benefit from this study’s findings by adopting fresh perspectives on TPACK and higher-order thinking.